2020
DOI: 10.1080/09553002.2020.1793016
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic low-dose environmental radiation on organ mass of bank voles in the Chernobyl exclusion zone

Abstract: Purpose: Animals are exposed to environmental ionizing radiation (IR) externally through proximity to contaminated soil and internally through ingestion and inhalation of radionuclides. Internal organs can respond to radioactive contamination through physiological stress. Chronic stress can compromise the size of physiologically active organs, but studies on wild mammal populations are scarce. The effects of environmental IR contamination on organ masses were studied by using a wild rodent inhabiting the Chern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
0
3
0
2
Order By: Relevance
“…Багато уваги приділяється вивченню фізіологічних (Einor et al, 2016), генетичних (Alexander, Bergendahl, 1964;Golub, Chernyk, 2008;Skorobagatko et al, 2020), у тому числі епігенетичних (Vaiserman, 2011;Guerrero-Bosagna et al, 2014) наслідків опромінення. Більшість досліджень було проведено в лабораторних умовах, але, як відзначають різні автори, їх результати не можна перенести на популяційні процеси (Козерецкая и др., 2008;Kivisaari et al, 2020). Дослідження дії радіації на біологічні об'єкти у природних популяціях мають певні особливості, серед яких можна відзначити наступне:…”
Section: вступunclassified
See 1 more Smart Citation
“…Багато уваги приділяється вивченню фізіологічних (Einor et al, 2016), генетичних (Alexander, Bergendahl, 1964;Golub, Chernyk, 2008;Skorobagatko et al, 2020), у тому числі епігенетичних (Vaiserman, 2011;Guerrero-Bosagna et al, 2014) наслідків опромінення. Більшість досліджень було проведено в лабораторних умовах, але, як відзначають різні автори, їх результати не можна перенести на популяційні процеси (Козерецкая и др., 2008;Kivisaari et al, 2020). Дослідження дії радіації на біологічні об'єкти у природних популяціях мають певні особливості, серед яких можна відзначити наступне:…”
Section: вступunclassified
“…(3) За думкою експертів (Garnier-Laplace et al, 2013;Mothersill et al, 2019;Kivisaari et al, 2020), дика природа може бути більш чутливою до іонізуючого опромінювання, ніж тварини, які використовуються в лабораторних дослідженнях, що пояснюється наявністю інших чисельних стресорів у природному середовищі.…”
Section: вступunclassified
“…Coincidentally, the coat color of bank voles is less red and lighter in color in more radioactive areas (Boraty ński et al 2014). A short selection of other important phenotypic effects includes reduced germination and seedling growth in wild carrots (Boraty ński et al 2016), shortened calling song in cuckoos (Møller et al 2016a), reduced growth rates in trees (Mousseau et al 2013), increased frequency of tumors and developmental abnormalities , increased prevalence of cataracts in the eyes of birds ) and rodents (Lehmann et al 2016), and decreased brain size in birds (Møller et al 2011) and voles (Kivisaari et al 2020).…”
Section: Phenotypic Effects Of Radiation Exposurementioning
confidence: 99%
“…A good example is the bank voles ( Myodes glareolus ) living in the Chernobyl Exclusion Zone (CEZ), for which a large number of studies showed that they are still experiencing individual functional modifications along the radioactive gradient more than 30 years after the nuclear power plant accident (e.g. colouration [ 32 ], cataracts [ 33 ], organ mass [ 34 ], DNA damage response [ 35 ]). These modifications were associated with decreased populations size [ 36 ] and thus question the impact on the vulnerability of populations in contaminated places.…”
Section: Introductionmentioning
confidence: 99%